Factors Predicting Outcomes After a Total Pancreatectomy and Islet Autotransplantation Lessons Learned From Over 500 Cases. Issue 4 (October 2015) - Chinnakotla, Srinath; Beilman, Gregory J.; Dunn, Ty B.; Bellin, Melena D.; Freeman, Martin L.; Radosevich, David M.; Arain, Mustafa; Amateau, Stuart K.; Mallery, J. Shawn; Schwarzenberg, Sarah J.; Clavel, Alfred; Wilhelm, Joshua; et al.
Abstract : Objective: Our objective was to analyze factors predicting outcomes after a total pancreatectomy and islet autotransplantation (TP-IAT). Background: Chronic pancreatitis (CP) is increasingly treated by a TP-IAT. Postoperative outcomes are generally favorable, but a minority of patients fare poorly. Methods: In our single-centered study, we analyzed the records of 581 patients with CP who underwent a TP-IAT. Endpoints included persistent postoperative "pancreatic pain" similar to preoperative levels, narcotic use for any reason, and islet graft failure at 1 year. Results: In our patients, the duration (mean ± SD) of CP before their TP-IAT was 7.1 ± 0.3 years and narcotic usage of 3.3 ± 0.2 years. Pediatric patients had better postoperative outcomes. Among adult patients, the odds of narcotic use at 1 year were increased by previous endoscopic retrograde cholangiopancreatography (ERCP) and stent placement, and a high number of previous stents (>3). Independent risk factors for pancreatic pain at 1 year were pancreas divisum, previous body mass index >30, and a high number of previous stents (>3). The strongest independent risk factor for islet graft failure was a low islet yield—in islet equivalents (IEQ)—per kilogram of body weight. We noted a strong dose-response relationship between the lowest-yield category (<2000 IEQ) and the highest (≥5000 IEQ or more). Islet graft failure was 25-fold more likely in the lowest-yield category. Conclusions: This article represents the largest study of factors predicting outcomes after a TP-IAT. Preoperatively, the patient subgroups we identified warrant further attention.